Global rising rates of caesarean sections. (5th March 2021) - Chien, Patrick
Abstract : Deputy Editor‐in‐Chief, Dr Patrick Chien, discusses how top articles from this issue in an audio podcast available at: https://soundcloud.com/bjog/april‐editors‐choice‐2021 .